An unattended HS-SPME-GC–MS/MS combined with a novel sample preparation strategy for the reliable quantitation of C8 volatiles in mushrooms: A sample preparation strategy to fully control the volatile emission. (15th June 2021) - Jung, Mun Yhung; Lee, Da Eun; Baek, Sun Hye; Lim, Su Min; Chung, Ill-Min; Han, Jae-Gu; Kim, Seung-Hyun
Highlights: A novel sample preparation for the complete control of volatile emission in mushrooms was developed. An unattended HS-SPME-GC–MS/MS was developed for accurate quantitation of C8 volatiles in mushrooms. The proposed method was reliable, sensitive, precise, and accurate. The profiles of C8 volatiles in mushrooms differed with mushroom species. Abstract: Eight carbon (C8) compounds are the key characteristic flavors of mushrooms. The quantitative analysis of the volatiles in mushrooms is challenging especially with the unattended HS-SPME-GC–MS. An unattended HS-SPME-GC–MS/MS in combination with novel sample preparation of the complete control of volatile emissions was developed for the quantitation of the C8 volatiles in mushrooms. The sample preparation strategy was composed of freeze-drying, rehydration, and the addition of a 15% citric acid solution. With this strategy, the volatile emission from mushroom was fully controlled at a certain time point. This method was found to be highly reliable, sensitive, precise, and accurate. This method was successfully applied to measure the contents of the C8 volatiles in the beech, button, and shiitake mushrooms. 1-Octene-3-ol was the most predominant compound in the mushrooms, representing 62.4, 69.0, and 89.2% of the total C8 volatiles in the beech, button, and shiitake mushrooms, respectively.